Francophone African cinema : history, culture, politics and theory - Frindéthié, Martial Kokroa (McFarland, 2009)
"This book offers a transnational and interdisciplinary analysis of 16 Francophone African films studied in the context of transnational conversations between African filmmakers and conventional theorists. It examines black French filmmakers' treatments of a number of cross-cultural themes, including intercontinental encounters and reciprocity, ideology and subjective freedom, governance and moral responsibility, sexuality and social order, and globalization"--Provided by publisher.